2011
DOI: 10.1021/jf104389m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Conventional Crop Rotation, Fertilization, and Crop Protection Practices on Metal Contents in Wheat (Triticum aestivum)

Abstract: The effects of organic versus conventional crop management practices (crop rotation, crop protection, and fertility management strategies) on wheat yields and grain metal (Al, Cd, Cu, Ni, Pb, and Zn) concentrations were investigated in a long-term field trial. The interactions between crop management practices and the season that the crop was grown were investigated using univariate and redundancy analysis approaches. Grain yields were highest where conventional fertility management and crop protection practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 38 publications
7
79
0
3
Order By: Relevance
“…Analyses for metals in wheat flours are therefore important from both a nutritional and a toxicological point of view. The multi-element contents of wheat grain are the result of many factors such as agricultural practices, genetic factors, soil characteristics, seasonal influences and contamination from anthropogenic sources (Adriano, 2001;Kirchmann et al, 2009;Cooper et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses for metals in wheat flours are therefore important from both a nutritional and a toxicological point of view. The multi-element contents of wheat grain are the result of many factors such as agricultural practices, genetic factors, soil characteristics, seasonal influences and contamination from anthropogenic sources (Adriano, 2001;Kirchmann et al, 2009;Cooper et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Kabata-Pendias (2001) reported that after the addition organic matter, Cu, Zn, Pb and Cd could accumulate in organic horizons of soil as stable forms. However, as reported by Cooper et al (2011), regular application of organic matter may reduce plant uptake of metals because addition of organic compounds to the soil could lead in increased chelation of metals reducing plant availability of them.…”
Section: Commonly Used Methodsmentioning
confidence: 97%
“…According to Harris and Taylor (2001), reduction in Cd accumulation in durum wheat seeds by Zn might be due to alleviation of Zn stress through application of Zn fertilizer. Cooper et al (2011) too have conducted a study with wheat and based on the results, they stressed a potential risk of higher levels of Cd accumulation if P-fertilizers with a higher Cd content are used. In accordance with their view, Thomas et al (2012) reported that heavy metal accumulation in the soil does not depend on levels of phosphate fertilizer but on the levels of heavy metal impurities in the phosphate fertilizer.…”
Section: Commonly Used Methodsmentioning
confidence: 99%
See 2 more Smart Citations